Maintaining Authenticity of AI-assisted Works for Indonesian and Philippines Creative Writing Learners: Students’ Experience and Reflection - Khristianto Khristianto; Ana Mae M. Monteza; Ambhita Dhyaningrum; Ilham Rabbani (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
The advance in artificial intelligence (AI) are significantly influencing various fields, including literature and creative writing. In Indonesia and the Philippines, AI is increasingly used to assist novice writers in creating fictional works. Employing a qualitative approach, the research utilizes data sources: fictional texts created by learners (high school and college students) using AI; the learners' perceptions of their creative process. The findings shows that the majority of submitted work was of good quality (65%), with 30% rated as